Pengaruh Penambahan Pakan Cacing Tanah (Lumbricus rubellus) terhadap Pertumbuhan Ikan Jelawat (Leptobarbus hoevenii) - Diah Suprihatin; Aceng Ruyani; Sutarno Sutarno; Urip Santoso; Euis Nursa’adah (Jurnal Biosilampari : Jurnal Biologi, 2024)
The aim of this research was to determine the growth rate of jelawat fish seeds with a combination of commercial feed (PF 1000) and additional feed for earthworms (L. rubellus), to determine the best dose of artificial feed (PF 1000) and additional feed. food for earthworms (L. rubellus). for the growth of jelawat fish (L. hoevenii). This research used a Completely Randomized Design (CRD) with 4 treatments, namely doses P1 (100% pellets), P2 (25% pellets + 75% earthworms), P3 (50% pellets + 50% L. rubellus), and P4 (75% pellets + 25% L. rubellus) carried out for 28 days. The results of the research showed that the addition of earthworms had a significant effect on the increase in weight, length and width of jelawat fish seeds. The best growth was obtained in the treatment P2 pellets 25% + L. rubellus 75%, (1) The body weight of the jelawat fish during the study reached (11.22 g), (2) the body length of the jelawat fish was (38.8 mm), and (3) Body width of jelawat fish (5.71 mm). Based on the research that has been carried out, it can be concluded that the addition of (L. rubellus) has a real influence on the growth of L. heovenii and the highest specific growth is P2 (25% pellets + 75% L. rubellus) with a Specific Growth Rate (SGR) value of 40.07 %, Survival Rate (SR) 100%, Feed Intake (IF) 56,1g and Feed Conversion Ratio (FCR) 1.73 g.